Career performance trajectories of Olympic swimmers: Benchmarks for talent development - Allen, S. V.; Vandenbogaerde, T. J.; Hopkins, W. G. (European Journal of Sport Science, 2014)
The age-related progression of elite athletes to their career-best performances can provide benchmarks for talent development. The purpose of this study was to model career performance trajectories of Olympic swimmers to develop these benchmarks. We searched the Web for annual best times of swimmers who were top 16 in pool events at the 2008 or 2012 Olympics, from each swimmer's earliest available competitive performance through to 2012. There were 6959 times in the 13 events for each sex, for 683 swimmers, with 10 ± 3 performances per swimmer (mean ± s). Progression to peak performance was tracked with individual quadratic trajectories derived using a mixed linear model that included adjustments for better performance in Olympic years and for the use of full-body polyurethane swimsuits in 2009. Analysis of residuals revealed appropriate fit of quadratic trends to the data. The trajectories provided estimates of age of peak performance and the duration of the age window of trivial improvement and decline around the peak. Men achieved peak performance later than women (24.2 ± 2.1 vs. 22.5 ± 2.4 years), while peak performance occurred at later ages for the shorter distances for both sexes (~1.5-2.0 years between sprint and distance-event groups). Men and women had a similar duration in the peak-performance window (2.6 ± 1.5 years) and similar progressions to peak performance over four years (2.4 ± 1.2%) and eight years (9.5 ± 4.8%). These data provide performance targets for swimmers aiming to achieve elite-level performance.